Deciphering spatial genomic heterogeneity at a single cell resolution in multiple myeloma - Merz, Maximilian; Merz, Almuth Maria Anni; Wang, Jie; Wei, Lei; Hu, Qiang; Hutson, Nicholas; Rondeau, Cherie; Celotto, Kimberly; Belal, Ahmed; Alberico, Ronald; Block, AnneMarie W.; Mohammadpour, Hemn; et al. (Nature communications, 2022)
Osteolytic lesions (OL) characterize symptomatic multiple myeloma. The mechanisms of how malignant plasma cells (PC) cause OL in one region while others show no signs of bone destruction despite subtotal infiltration remain unknown. We report on a single-cell RNA sequencing (scRNA-seq) study of PC obtained prospectively from random bone marrow aspirates (BM) and paired imaging-guided biopsies of OL. We analyze 148,630 PC from 24 different locations in 10 patients and observe vast inter- and intra-patient heterogeneity based on scRNA-seq analyses. Beyond the limited evidence for spatial heterogeneity from whole-exome sequencing, we find an additional layer of complexity by integrated analysis of anchored scRNA-seq datasets from the BM and OL. PC from OL are characterized by differentially expressed genes compared to PC from BM, including upregulation of genes associated with myeloma bone disease like DKK1 , HGF and TIMP-1 as well as recurrent downregulation of JUN/FOS , DUSP1 and HBB . Assessment of PC from longitudinally collected samples reveals transcriptional changes after induction therapy. Our study contributes to the understanding of destructive myeloma bone disease. Osteolytic lesions (OL) are frequent in multiple myeloma (MM), but are poorly understood. Here, the authors characterise OLs in MM patient samples using single-cell RNA-seq, revealing genes that are specifically regulated in OL compared to random bone marrow aspirates and that reflect the response to induction therapy.